Functionalized Graphene Fiber Modified With MOF-Derived Rime-Like Hierarchical Nanozyme for Electrochemical Biosensing of H2O2 in Cancer Cells - Huang, Wei; Xu, Yun; Sun, Yimin (Frontiers in Chemistry, 2022)
The rational design and construction of high-performance flexible electrochemical sensors based on hierarchical nanostructure functionalized microelectrode systems are of vital importance for sensitive in situ and real-time detection of biomolecules released from living cells. Herein, we report a novel and facile strategy to synthesize a new kind of high-performance microelectrode functionalized by dual nanozyme composed of rime-like Cu2(OH)3NO3 wrapped ZnO nanorods assembly (Cu2(OH)3NO3@ZnO), and explore its practical application in electrochemical detection of hydrogen peroxide (H2O2) released from living cells. Benefiting from the merits of the unique hierarchical nanohybrid structure and high catalytic activities, the resultant Cu2(OH)3NO3@ZnO modified AGF microelectrode shows remarkable electrochemical sensing performance towards H2O2 with a low detection limit of 1 µM, and a high sensitivity of 272 μA cm-2 mM-1, as well as good anti-interference capability, long-term stability and reproducibility. These properties enabled the proposed microelectrode based electrochemical platform to be applied for in situ amperometric tracking H2O2 released from different types of human colon cells thus demonstrating its great prospect as a sensitive cancer cell detection probe for early diagnosis and management of various cancer diseases.